2018
DOI: 10.1186/s40359-018-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Personal wellbeing in posttraumatic stress disorder (PTSD): association with PTSD symptoms during and following treatment

Abstract: BackgroundIt remains unclear to what extent treatment-related gains in posttraumatic stress disorder (PTSD) symptoms translate to improvements in broader domains of personal wellbeing, such as community connectedness, life achievement and security. We sought to determine whether: 1. personal wellbeing improves during the course of a treatment program and 2. changes in core symptom domains (PTSD, anxiety and depression) were associated with improvements in overall personal wellbeing.MethodsParticipants (N = 124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
11
1
1
Order By: Relevance
“…The workers’ PTSS and subjective well-being were negatively correlated, as expected, in accordance with the current literature (Berle et al, 2018). As for the relations between dyadic coping and PTSS, results showed that the higher the use of some types of dyadic coping by the workers who had suffered a work accident, such as Stress Communication (partner), Supportive DC (both self and partner) and Delegated DC (self), and of Stress Communication (self) and Delegated DC (partner) by the partners, the lower the PTSS levels.…”
Section: Discussionsupporting
confidence: 92%
“…The workers’ PTSS and subjective well-being were negatively correlated, as expected, in accordance with the current literature (Berle et al, 2018). As for the relations between dyadic coping and PTSS, results showed that the higher the use of some types of dyadic coping by the workers who had suffered a work accident, such as Stress Communication (partner), Supportive DC (both self and partner) and Delegated DC (self), and of Stress Communication (self) and Delegated DC (partner) by the partners, the lower the PTSS levels.…”
Section: Discussionsupporting
confidence: 92%
“…Third, comparative studies are needed to determine if psychodrama group therapy could be used as an alternative or supplemental treatment to more traditional trauma-informed treatment approaches. The closest comparison that we could find to the current programming was a 4-week traumafocused CBT residential program (Berle et al, 2018), which showed a mean decrease in PTSD (using PCL) at 5.85 (9.32% decrease). In comparison, the current trauma-focused psychodrama program demonstrated a decrease in PTSD of 14.57 points (25.49% decrease).…”
Section: Trauma-focused Psychodrama and Ptsdmentioning
confidence: 84%
“…In addition to this reason, STAIR‐PC was developed to target PTSD, yet PTSD is just one diagnosis among many, and symptom reduction may have only a small immediate impact on perceived quality of life. Previous studies suggest that PTSD symptom reduction may lead to improvements in other life domains at longer‐term follow‐up (Berle et al, 2018; Rapaport, Endicott, & Clary, 2002; Schnurr, Hayes, Lunney, McFall, & Uddo, 2006). Therefore, our postintervention assessment may not have captured changes in quality of life that may be present at follow‐up data.…”
Section: Discussionmentioning
confidence: 99%